The Effectiveness of “GAMAK” in Overcoming Early Marriage in Gegerung Village Lingsar District - Hulfa, Diana; Rahmadi, Didin Septa; Ningsih, Dewi Puspita; Apriawan, Andika; Suryadmaj, Galih (International Journal of Social Sciences and Humanities, 2023)
This study is a descriptive qualitative study that aims to examine the effectiveness of gamak in overcoming early marriage in Gegerung Village, Lingsar District. The data sources for this study are the Village Head, Hamlet Head, Neighborhood Association, Parents and some of the people of Gegerung Village who are involved. Data collection was carried out using interview, documentation, and observation methods. Furthermore, the data obtained was analyzed using interactive model data analysis. In order to obtain data validity, triangulation was carried out. The results of the study showed that from year to year the number of merarik kodeq decreased since the Gamak program was implemented. The supporting factors felt by the Village were because there was already a Law regulating the prohibition of underage marriage, the NTB Governor's Regulation and the West Lombok Regent's Regulation concerning Underage Marriage. The obstacles faced by the Village were social media and free association. The role of the Village Government in minimizing early marriage is by always providing socialization and education about the dangers of early marriage. Although, in the early years of the implementation of the Gamak program, the cases of merarik kodeq were still relatively high, due to the process of socializing the program to the community and so on. From 2022 to 2023, there was a decrease in cases, although not significantly. There was a different cycle per year related to the merarik kodek cases that occurred in Gegerung Village, Lingsar District.